Prognostic role of circulating tumor cells in patients with EGFR‐mutated or ALK‐rearranged non‐small cell lung cancer. Issue 5 (27th March 2018) - Tong, Bing; Xu, Yan; Zhao, Jing; Chen, Minjiang; Zhong, Wei; Xing, Jia; Wang, Mengzhao
Abstract : Background: Circulating tumor cell (CTC) counts at baseline and follow‐up are an independent prognostic factor in patients receiving standard chemotherapy for non‐small cell lung cancer (NSCLC). This study further explored the role of CTCs in EGFR ‐mutated and ALK ‐rearranged NSCLC patients administered targeted therapies as first‐line treatment. Methods: CTCs were enumerated with a novel high‐efficiency detection method from the blood of 43 patients with EGFR ‐mutated or ALK ‐rearranged NSCLC at baseline and at disease‐progression. Patients were stratified into favorable and unfavorable groups with baseline CTC counts of < 8 or ≥ 8 CTCs/3.2 mL, respectively. Results: A total of 76.7% of the patients were positive for ≥ 2 CTCs /3.2 ml blood at baseline. The median progression‐free survival (PFS) and overall survival (OS) rates of the favorable compared to the unfavorable group were longer (11.6 vs. 8.5 months, P = 0.004 for PFS; 21.00 vs. 17.7 months, P = 0.013 for OS). Multivariate analysis demonstrated that baseline CTC count was a strong predictor of PFS (hazard ratio 2.835; 95% confidence interval 1.240–6.483; P = 0.014) and OS (hazard ratio 3.317; 95% confidence interval 1.360–8.092; P = 0.008). Conclusion: Baseline CTC count could be a predictive biomarker for EGFR ‐mutated and ALK ‐rearranged NSCLCs, which allows for better guidance and monitoring of patients over the course of molecular targeted therapies.